Should history change the way we think about populism? - Alan De Bromhead; Kevin Hjortshøj O'Rourke (Queen's University Centre for Economic History (QUCEH), 2023)
This paper asks whether history should change the way in which economists and economic historians think about populism. We use Müller's definition, according to which populism is 'an exclusionary form of identity politics, which is why it poses a threat to democracy'. We make three historical arguments. First, late 19th century US Populists were not populist. Second, there is no necessary relationship between populism and anti-globalization sentiment. Third, economists have sometimes been on the wrong side of important policy debates involving opponents rightly or wrongly described as populist. History encourages us to avoid an overly simplistic view of populism and its correlates.
Keywords: D72; N40; N70; 330; populism; globalization; economists; history